2003
DOI: 10.1095/biolreprod.102.008730
|View full text |Cite
|
Sign up to set email alerts
|

Cloned Mice Derived from Embryonic Stem Cell Karyoplasts and Activated Cytoplasts Prepared by Induced Enucleation

Abstract: Our objective was to induce enucleation (IE) of activated mouse oocytes to yield cytoplasts capable of supporting development following nuclear transfer. Fluorescence microscopy for microtubules, microfilaments, and DNA was used to evaluate meiotic resumption after ethanol activation and the effect of subsequent transient treatments with 0.4 micro g/ml of demecolcine. Using oocytes from B6D2F1 (C57BL/6 x DBA/2) donors, the success of IE of chromatin into polar bodies (PBs) was dependent on the duration of deme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
45
0

Year Published

2004
2004
2011
2011

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(50 citation statements)
references
References 24 publications
5
45
0
Order By: Relevance
“…The observed efficiencies of ESC derivation from our control embryos are similar to those previously reported by Gong et al (2008) in the hybrid B6CBAF1 strain, which was 15.3% for parthenogenetic blastocysts. Owing to the infrequent use of hybrid B6CBAF1 animals in SCNT experiments (Gasparrini et al 2003, Maalouf et al 2009, Costa-Borges et al 2010, no ntESC lines have been derived from this genetic background until now, but the efficiencies obtained in ntESC derivation in this study are similar to those reported for other hybrid strains (Wakayama et al 2005).…”
Section: Discussionsupporting
confidence: 69%
See 2 more Smart Citations
“…The observed efficiencies of ESC derivation from our control embryos are similar to those previously reported by Gong et al (2008) in the hybrid B6CBAF1 strain, which was 15.3% for parthenogenetic blastocysts. Owing to the infrequent use of hybrid B6CBAF1 animals in SCNT experiments (Gasparrini et al 2003, Maalouf et al 2009, Costa-Borges et al 2010, no ntESC lines have been derived from this genetic background until now, but the efficiencies obtained in ntESC derivation in this study are similar to those reported for other hybrid strains (Wakayama et al 2005).…”
Section: Discussionsupporting
confidence: 69%
“…The discrepancy of results in the mouse species can be probably attributed to strain-specific differences, as not all HDACis are equally effective in all genetic backgrounds (Kishigami et al 2007, Van Thuan et al 2009). With regard to the IE procedure, although Gasparrini et al (2003) previously reported the production of a cloned mouse using cytoplasts prepared by IE, we were unable to obtain live offspring from the IE group. It should be mentioned, however, that they used ESCs as karyoplast donors, which are known to be easier to reprogram than the cumulus cells used in our study (Hochedlinger & Jaenisch 2006).…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…To synchronize the fused tetraploid embryos into metaphase, we used the microtubule-destabilizing agent DC, which was previously used for induced enucleation in nuclear transfer experiments [11,[29][30]. Regardless of the polyploidizing nature of DC [31], no reports regarding its effects on full-term embryo development were available.…”
Section: Discussionmentioning
confidence: 99%
“…The cleavage time of the tetraploid embryos is strongly correlated with diploid embryo cleavage time (Supplementary information, Table S1). Synchronized tetraploid embryos with two distinct nuclei (obtained from blastomeres) were generated in media containing demecolcine (DC), a colchicine-related drug that depolymerizes microtubules and limits spindle formation during metaphase (Supplementary information, Table S2) [11]. This process appeared to be reversible, since the tetraploid embryos could regain mitotic activity and continue through repeated cell cycles upon release from DC exposure (Supplementary information, Table S3).…”
Section: Tetraploid Embryo Cell Cycle Synchronizationmentioning
confidence: 99%